Intentionality, Morality, and the Incest Taboo in Madagascar - Sousa, Paulo; Swiney, Lauren (Frontiers in Psychology, 2016)
In a recent article (Astuti & Bloch, 2015), cognitive anthropologists Rita Astuti and Maurice Bloch claim that the Malagasy are ambivalent as to whether considerations of intentionality are relevant to moral judgments concerning incest and its presumed catastrophic consequences: when making moral judgments about those who commit incest, the Malagasy take into account whether the incest is intentional or not, but, when making moral judgments relating to incest’s catastrophic consequences, they do not take intentionality into account. Astuti & Bloch explain the irrelevance of intentionality in terms of incest entailing such a fundamental attack on the transcendental social order that the Malagasy become dumbfounded and leave aside considerations of intentionality. Finally, they claim that a similar dumbfound reaction is what is involved in the moral dumbfounding concerning incest that social psychologist Jonathan Haidt has found in the US. In this paper, we argue that (i) Astuti & Bloch are unclear about many aspects of their claims (in particular, about the moral judgments at stake), (ii) they do not provide sufficient evidence that considerations of intentionality are deemed irrelevant to moral judgments relating to incest’s presumed catastrophic consequences (and hence for the claim that the Malagasy are ambivalent), (iii) their hypothesis that conceiving of incest as an attack on the transcendental social renders considerations of intentionality irrelevant lacks coherence, and (iv) the extension of their explanatory account to the moral dumfounding of American students in Haidt’s well-known scenario of intentional incest is unwarranted.